Transition of CPW to SINRD guide of PCB version. Issue 4 (April 2017) - Hu, Xiaojun; Li, Fan; Xu, Feng
ABSTRACT: Substrate integrated nonradiative dielectric (SINRD) waveguide fabricated directly on printed circuit board (PCB) or metalized dielectric layer, with its excellent performances of simplifying fabrication process and minimizing mechanical errors, is vitally essential at the microwave and millimeter‐wave frequencies. In this article, a transition of coplanar waveguides (CPW) to the SINRD waveguides based is presented, providing effective interconnects for compactly and flexibly integrating the planar‐CPW‐based devices with the SINRD waveguide circuits. It is found that simulated results are in good agreements with the measured results, which proves the promising future of the SINRD waveguide of PCB version in the area of millimeter‐wave hybrid integrated systems. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:898–900, 2017